login

Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 61st year, we have over 378,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”).

a(n) = 9 a (n-1)-26 a(n-2) +24 a(n-3) (n >= 3) with a(0) =a(1)=1, a(2)=2.
0

%I #6 Mar 30 2012 17:40:04

%S 1,1,2,16,116,676,3452,16276,72956,316276,1340252,5590036,23054396,

%T 94314676,383578652,1553331796,6270493436,25253701876,101530450652,

%U 407669649556,1635323974076,6555235693876,26262769508252

%N a(n) = 9 a (n-1)-26 a(n-2) +24 a(n-3) (n >= 3) with a(0) =a(1)=1, a(2)=2.

%C The above sequence also satisfies a(n)-6 a(n-1)+8 a(n-2)=4*3^{n-2} (n >= 3) with a(0)= a(1)=1.

%F a(n)=7*2^(n-1)+3*2^(2*n-1)-4*3^n. G.f.: -(1-8*x+19*x^2)/((3*x-1)*(2*x-1)*(4*x-1)) [From _R. J. Mathar_, Jul 13 2009]

%K nonn

%O 0,3

%A Tian-Xiao He (the(AT)iwu.edu), Jul 11 2009

%E More terms from Vincenzo Librandi and _R. J. Mathar_, Jul 13 2009